English Consonant Errors Pronounced by Seventh Grade Students in Dwijendra High School - Yohanes Octovianus L. Awololon; Ni Made Diana Erfiani; Ni Luh Desy Suari Dewi; Komang Satria Wirasa (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
The study aimed to identify and analyze the errors made by seventh-grade students at SMP Dwijendra Denpasar in pronouncing certain English consonants, which are essential components of their target language learning. The study specifically focuses on the student’s articulation of six English contoid consonants: [ʃ], [ʧ], [θ], [ʒ], [ʤ], and [ð]. A qualitative descriptive method was applied in this research, involving several stages: collecting data from the students as research subjects, organizing and constructing the data for analysis, interpreting the results, and drawing relevant conclusions. The research findings revealed that no students could pronounce the targeted consonants accurately according to standard English pronunciation norms. The articulation errors were mainly caused by various influencing factors, including interlingual transfer, where the students’ first language interferes with their pronunciation of English sounds, and intralingual factors, which refer to difficulties arising from the complexities within the English language. However, the mispronunciation of key consonant sounds created misunderstandings and affected the clarity of their spoken language. As a result, these errors posed a challenge in achieving effective oral communication as a critical aspect of mastering a second language. The findings emphasized the importance of addressing these pronunciation challenges through targeted interventions and improved teaching strategies to enhance students’ language proficiency and communication skills.